Siderophores, a potential phosphate solubilizer from the endophyte Streptomyces sp. CoT10, improved phosphorus mobilization for host plant growth and rhizosphere modulation. (20th September 2022) - Cui, Kunpeng; Xu, Ting; Chen, Jiawei; Yang, Haiyu; Liu, Xuanming; Zhuo, Rui; Peng, Yinghe; Tang, Wei; Wang, Rui; Chen, Longsheng; Zhang, Xuan; Zhang, Zhen; et al.
Abstract: Available phosphorus (AP) deficiency in soil is an important limiting factor in agricultural and forestry production. Thus, microbes with high P mobilization capacity are of great concern, especially for acidic soil where most P is fixed by Fe. Camellia oleifera is a typical acidic soil–planted oil crop with a high status in forestry economic systems in China. In this study, Streptomyces sp. CoT10 was screened and identified from C. oleifera endophytes. CoT10 could effectively mobilize different P resources, particularly showing a high solubility of 72.49 mg L −1 for FePO4, and was prominent in the production of different siderophores. Here, we initially assumed and confirmed that the Fe–P mobilization function of CoT10 was directly mediated by its siderophores. Application of CoT10 in C. oleifera could benefit P fraction transformation by mobilizing insoluble P and Fe, thus improving 15.35% AP content in soil and promoting plant growth with high P and Fe acquisition. In addition, CoT10 inoculation improved microbial diversity, with the proportions of some dominant groups, such as Actinobacteria, Proteobacteria, and Firmicutes, obviously enriched by 21.32%, 7.93%, and 38.95%, respectively. In addition, redundancy analysis (RDA), network analysis and functional prediction indicated that CoT10 inoculation improved the microbial interactions in C. oleifera rhizosphere soil and balanced the soil microbial P- and Fe-related functional roles. The results of Streptomyces sp. CoT10 and its siderophores provide a valuable approach to regulate P mobilization in iron-rich soil for the sustainable and eco-friendly development of plant-related industries. Graphical abstract: Image 1 Highlights: Endophyte Streptomyces sp. CoT10 mobilizes insoluble Fe-fixed P through siderophores. CoT10 broadly improves AP content for soils from various regions in southern China. CoT10 benefits soil bacterial community and P-cycling function. Microbial siderophores provide a novel approach to solve P-deficient problem in soil.